2014
DOI: 10.4236/wjns.2014.41003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of migraine among university students at Parakou, Benin: A cross-sectional study

Abstract: Objective: To determine the prevalence of migraine and its associated factors in students at the University of Parakou. Methods: It was a cross-sectional study carried out from February 1st to April 30th 2011. It included all students registered during the academic year 2010-2011 and selected by systematic random sampling. Migraine was defined according to IHS 2004 criteria. To assess the link between migraine and body mass index we collected height and weight of each student. Multivariate analysis was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
6
10
1
2
Order By: Relevance
“…(14) Different of Adoukonou et al who in the city of Parakou (West Africa) demonstrated that university students presented 62% of this characteristic for migraine without and with aura, and the two migraines were not separated as to the duration of the crisis. (13) The prevalence of the type of pain (throbbing/pulsatile) was evidenced in 40% of the academics in this study (Table 3), different from the study of Galvez et al that showed 77,3% of throbbing/pulsatile pain in medical students with migraine without aura in a university of Lima (Peru), being greater than this study.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…(14) Different of Adoukonou et al who in the city of Parakou (West Africa) demonstrated that university students presented 62% of this characteristic for migraine without and with aura, and the two migraines were not separated as to the duration of the crisis. (13) The prevalence of the type of pain (throbbing/pulsatile) was evidenced in 40% of the academics in this study (Table 3), different from the study of Galvez et al that showed 77,3% of throbbing/pulsatile pain in medical students with migraine without aura in a university of Lima (Peru), being greater than this study.…”
Section: Discussioncontrasting
confidence: 55%
“…The authors justify the value found for the cultural reasons, the triggering factors and the methods of study. (13) Andrade et al classified medical students as having or not having migraine. Representing for students with migraine, a result of 8,6%, being a lower prevalence of migraine than the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Migraine, like other primary headaches, affects all socioprofessional classes [20,23,38]. In our study, migraine affects all occupations but with a predominance for informal sector workers (32.2%) and students / students (31.7%).…”
Section: Discussionmentioning
confidence: 54%
“…Most other African data come from studies of more specific populations; school children, workers, etc. [18][19][20].…”
Section: Discussionmentioning
confidence: 99%